Collaborative Project Based Learning Model in English Learning - Jaya, Aswadi; Mortini, Asti Veto (LPPM Undiksha, 2023)
In news writing, there are problems with writing skills that are often found in the world of national education. Collaborative, project-based learning models have proven useful for learning English and writing news. Therefore this development research aims to create a project-based learning product model. The Borg & Gall development procedure is followed in this research process. Students and instructors of English study program served as the research subjects. This development method results in reliable, usable, and efficient project-based learning model products for learning to write news stories. In order to collect data for this study, a questionnaire was presented to two material specialists and two media experts. The following are the findings from a study that looked at the viability of developing a project-based learning product learning model for learning how to write news using a Likert scale with a score range of 1 to 5. The results of material experts' validation received a score of 81.54%, placing them in the